Diabetic retinopahty: knowledge, attitude and practice - Giri, Puspa; Sah, Ranjeet; Shrestha, Manisha; Munsuri, Raja Husain; Dhital, Bishnu Mani; Ranabhat, Sudha (Journal of Chitwan Medical College, 2021)
Background: Diabetes Mellitus is a metabolic disorder with a multisystemic involvement such as heart, blood vessels, kidneys, nerves including eyes where, hyperglycemia causes loss of pericytes and thus damages retinal capillaries leading to diabetic retinopathy. The aim of this study was to access knowledge, attitude and practice pattern in diabetes patients residing in Chitwan and neighboring districts. Methods: A community based cross-sectional study was carried out involving diabetes mellitus patients in three districts namely Chitwan, Nawalpur and Gorkha province along with patients who were referred to the hospital. Questionnaire were provided to the patients that accessing knowledge about the ocular complications, attitude and practice concerning diabetes and diabetic retinopathy. General systemic and ocular examinations were performed, including assessment of random blood sugar. The data was collected from March 2019 to June 2019. The collected data analyzed using Statistical Package for Social Studies (SPSS) version 11 (Armonk, IBM, USA). Results: This study included 500 patients, ranging from 30-85years. Diabetes mellitus was diagnosed at an average age of 60.52±11.47 years (32-89 years) who were mostly being treated with an oral-hypoglycemic agents. About 95.2% of the patients in the screening camp and 96.4% from hospital were aware regarding the ocular complication in diabetes. Diabetic retinopathy prevalence was observed in 28% of the patients out of which 26% were from screening camp and 14.8% were from hospital, in whom bilateral ocular involvement were frequently observed. Conclusions: The knowledge and attitude of the patient in our study were found to be adequate towards the diabetes and diabetic retinopathy. Nonetheless, this was not executed well in daily practice by the respondents.